PENGEMBANGAN WEB PEMBELAJARAN BERBASIS GOOGLE SITE UNTUK MENINGKATKAN LITERASI BACA TULIS PESERTA DIDIK KELAS 5 DI SDN 2 SELONG - Didi Darmaji Nurdiansah; Muhammad Makki; Setiani Novitasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to produce learning media based on Google Site to improve Reading and Writing Literacy in grade 5 SDN 2 Selong which is valid, practical and effective. This research is a type of R&D (Research and Development) research using the ADDIE development model (Analysis: determining learning needs and goals to be achieved, Design: planning and designing learning materials, strategies, and activities. Development: developing and producing learning materials, Implementation: delivering learning materials to students, and Evaluation: evaluating the effectiveness of learning and making revisions if needed). The subject of this research is grade 5 students of SDN 2 Selong as many as 30 people. Meanwhile, the object of this research is google site learning media for reading and writing literacy material. The research instruments used were questionnaire sheets for media experts and material experts to determine the validity of google site learning media, and student responses to determine the practicality of google site learning media, tests to measure the level of students' classical learning completeness. The results of this study showed that google site-based learning media obtained a percentage of 90% with very valid criteria from media experts, a percentage of 86.67% with very valid criteria from material experts, a score of 169.1 with very good / practical criteria from student responses, and a percentage of 96.7% effective criteria from the results of student learning tests calculated by classical learning completeness and a percentage of 64% and an average of 0.64 with moderately effective criteria from the n-gain test results for increasing students' reading and writing literacy after using google site media. Therefore, it can be concluded that the google site-based learning media for reading and writing literacy material is feasible from the aspects of validity, practicality and effectiveness to be used as a learning media in grade 5 SDN 2 Selong. As well as increasing students' literacy in reading and writing is quite effective in the learning process.